2015
DOI: 10.1021/am505861c
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Cu2O@TiO2 Composite Photocatalysts with pn Heterojunctions Formed on Exposed Cu2O Facets, Their Energy Band Alignment Study, and Their Enhanced Photocatalytic Activity under Illumination with Visible Light

Abstract: The creation of photocatalysts with controlled facets has become an important approach to enhance their activity. However, how the formation of heterojunctions on exposed facets could affect their photocatalytic performance ranking had not yet been investigated. In this study, Cu2O@TiO2 core-shell structures were created, and Cu2O/TiO2 p-n heterojunctions were formed on various exposed facets of Cu2O cubes, Cu2O cuboctahedra, and Cu2O octahedra, respectively. These Cu2O@TiO2 polyhedra demonstrated an enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(86 citation statements)
references
References 52 publications
1
85
0
Order By: Relevance
“…Moreover, it was found that Cu 2 O@TiO 2 core-shell photocatalysts had different band offset values ( Figure 16C), demonstrating a clear facet-dependent activity. The photocatalytic performance of Cu 2 O@TiO 2 polyhedra was different with that of pure Cu 2 O polyhedra without TiO 2 shells, which could be attributed to the different driving forces for the charge carrier separation [105]. …”
Section: Cu 2 O-tio 2 Heterojunctionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, it was found that Cu 2 O@TiO 2 core-shell photocatalysts had different band offset values ( Figure 16C), demonstrating a clear facet-dependent activity. The photocatalytic performance of Cu 2 O@TiO 2 polyhedra was different with that of pure Cu 2 O polyhedra without TiO 2 shells, which could be attributed to the different driving forces for the charge carrier separation [105]. …”
Section: Cu 2 O-tio 2 Heterojunctionmentioning
confidence: 92%
“…Moreover, it was found that Cu2O@TiO2 core-shell photocatalysts had different band offset values ( Figure 16C), demonstrating a clear facet-dependent activity. The photocatalytic performance of Cu2O@TiO2 polyhedra was different with that of pure Cu2O polyhedra without TiO2 shells, which could be attributed to the different driving forces for the charge carrier separation [105]. It is well known that controlled morphology by application of exposed facets (faceted semiconductors) significantly enhances photocatalytic performance, due to excellent crystallinity and low content of defects, e.g., octahedral and decahedral anatase particles [103,104].…”
Section: Cu 2 O-tio 2 Heterojunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroaromatic compounds are widely used as synthetic intermediates in the manufacture of pharmaceuticals, fungicides, pesticides, plasticizers, and dyes and are regarded as water pollutants owing to their presence in industrial effluents [43]. 4-Nitrophenol (4-NP)-one of the most important nitroaromaticshas been listed as a "priority pollutant" by the US Environmental Protection Agency because it is highly soluble, has good chemical stability, and is not easily removed by natural degradation.…”
Section: Nano Resmentioning
confidence: 99%
“…[9] Cuprous oxide (Cu 2 O) has been applied as an attractive photoelectrode material for Page 4 of 30 A c c e p t e d M a n u s c r i p t 4 hydrogen production, because Cu 2 O is a p-type semiconductor with narrow bandgap (1.9-2.2 eV) of which the conduction band and valence band are close to the reduction and oxidation potential for water splitting. [10][11][12][13] As previous reports, [14,15] wide bandgap semiconductor (such as TiO 2 and ZnO) modified with Cu 2 O nanoparticles can significantly expand their absorption spectra range. However, the low interfacial area between different semiconductors directly influenced the separation efficiency of electrons and holes, so interfacial optimization of heterogeneous becomes a feasible way to further improving photoelectrochemical conversion efficiency.…”
Section: Introductionmentioning
confidence: 71%